2017
DOI: 10.3390/genes8060156
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of Salinity Stress-Responsive miRNAs in Wild Emmer Wheat (Triticum turgidum ssp. dicoccoides)

Abstract: MicroRNAs (miRNAs) are a class of endogenous small noncoding RNAs which regulate diverse molecular and biochemical processes at a post-transcriptional level in plants. As the ancestor of domesticated wheat, wild emmer wheat (Triticum turgidum ssp. dicoccoides) has great genetic potential for wheat improvement. However, little is known about miRNAs and their functions on salinity stress in wild emmer. To obtain more information on miRNAs in wild emmer, we systematically investigated and characterized the salini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…During this investigation, qRT-PCR indicated that seven miRNAs have different expression models in both leaves and root of plants under stress and normal conditions. This is in accordance to prior results reported in wheat and rice [38,39]. In fact, miRNAs are expressed only in some organs and in response to environmental stresses [40,41].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…During this investigation, qRT-PCR indicated that seven miRNAs have different expression models in both leaves and root of plants under stress and normal conditions. This is in accordance to prior results reported in wheat and rice [38,39]. In fact, miRNAs are expressed only in some organs and in response to environmental stresses [40,41].…”
Section: Discussionsupporting
confidence: 93%
“…The miR408 family was suggested as Cu-miRNA [37]. In Arabidopsis at low and high Cu concentration, Cu-miRNA accumulated and disappeared, respectively [38,39].The main target genes of miR408 encode blue copper proteins, including those in the phycocyanin family [53,54]. The biological function of Cu is entirely related to the reconstruction of its properties.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, all the seven DECs had 2–13 miRNA-binding sites, which was similar with previous reports in human and another study in wheat [ 23 , 26 ], but was significantly higher than that reported in rice and tomato [ 18 , 19 ]. Interestingly, some putative circRNA-binding miRNAs have been reported that involved in the response to low nitrogen and other abiotic stresses [ 37 , 38 ]. For example, miR530 is differentially expressed in response to low nitrogen stress in rice, suggesting that it may play an important role in plant nitrogen utilization [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In alfalfa, miR156 regulates shoot branching, stem thickness, trichome density, flowering time and forage yield (Aung et al , ). In addition to growth and development, miR156 has been associated with response to salinity and drought in A. thaliana , Brachypodium distachyon, cotton, rice, barley, wheat and alfalfa (Wang et al , Cui et al , Mondal and Ganie , Deng et al , Arshad et al , Feng et al ); aluminum stress in rice (Lima et al ); and immunity to bacterial infection in Nicotiana benthamiana (Padmanabhan et al ). The above‐mentioned observations suggest that miR156 could also be an effective molecular tool to improve heat stress in plants (Aung et al , Gao et al , Arshad et al ).…”
Section: Introductionmentioning
confidence: 99%